DAMPAK INVESTASI SWASTA DAN PUBLIK TERHADAP PENGURANGAN KEMISKINAN (STUDI KASUS: PROVINSI PENGHASIL NIKEL DI INDONESIA) - Talmera, Daniel Ananta (FISIP UWP, 2024)
The aim of this study is concluding whether the realization of public investment and private investment has reduced the number of poverties in Nickel Producing Provinces in Indonesia. By using 4 cross-province data from 2013 to 2022. This paper examines the relationship between the foreign direct investment realization, domestic direct investment realization, public investment and the number of poverty. By using Regression Analysis we found that domestic direct investment has significant effect on poverty reduction. Meanwhile foreign direct investment Realization and public investment realisation has no significant effect on poverty reduction in South Sulawesi, Central Sulawesi, Southeast Sulawesi and North Maluku